Physics and Technology of Silicon Carbide Devices - Hijikata, Yasuto (IntechOpen, 2012)
Recently, some SiC power devices such as Schottky-barrier diodes (SBDs), metal-oxide-semiconductor field-effect-transistors (MOSFETs), junction FETs (JFETs), and their integrated modules have come onto the market. However, to stably supply them and reduce their cost, further improvements for material characterizations and those for device processing are still necessary. This book abundantly describes recent technologies on manufacturing, processing, characterization, modeling, and so on for SiC devices. In particular, for explanation of technologies, I was always careful to argue physics underlying the technologies as much as possible. If this book could be a little helpful to progress of SiC devices, it will be my unexpected happiness.